Academic Writing Instruction in Eastern Indonesia: A Multi-Stakeholder Needs Analysis of Tertiary EFL Learners - Ummu Rofikah (Pendiri: Jurnal Riset Pendidikan, 2026)
Academic writing instruction in EFL higher education is often planned without comparing learners’ perceptions with the expectations of more experienced stakeholders. This study examined perceived needs for academic writing instruction at UIN Alauddin Makassar, Eastern Indonesia, and identified areas of convergence and divergence among 51 fourth-semester students, 100 senior students who had completed an academic writing course, and two academic writing lecturers. A quantitative descriptive needs-analysis design used a structured questionnaire covering perceived EFL proficiency, the importance and goals of academic writing, confidence in writing tasks, preferred topics, and instructional activities. Frequencies, percentages, and mean scores were calculated separately for each group and compared descriptively across stakeholder groups. All groups viewed academic writing as important and identified summarizing and paraphrasing as a shared area of low confidence. However, they differed in evaluations of critical source use and preferred learning activities: senior students prioritized workshops and AI-assisted learning, whereas lecturers favored peer review and individual writing tasks. The study contributes a context-sensitive, multi-stakeholder account that connects needs analysis with academic literacy by showing that perceived general EFL proficiency does not necessarily indicate readiness for source-based academic writing. The findings support instruction that combines diagnostic assessment, explicit source-literacy development, scaffolded feedback, and carefully guided technology use. Because the evidence is perception-based and drawn from one institution, the results represent reported needs rather than direct measures of writing performance.